نبی ﷺ کا اندازِ گفتگو : ایک علمی و تحقیقی جائزہ: The Prophetic Style of Speech: A Scholarly and Analytical Study (Al-Qamar, 2025)
Effective communication plays a central role in shaping human relationships, social harmony, and moral development. In Islamic teachings, communication is not merely a tool for conveying information but a moral and ethical responsibility. This research paper explores the communication style of Prophet Muhammad (peace be upon him) as a comprehensive and exemplary model of human interaction. The study aims to analyze the fundamental characteristics of the Prophet’s mode of conversation, including clarity, simplicity, brevity, politeness, emotional intelligence, and respect for listeners, as derived from the Quran, Hadith and authentic Seerah literature. Using a qualitative and analytical research approach, the paper examines classical Islamic sources alongside contemporary academic studies on prophetic communication. The findings indicate that the Prophet’s communication was audience-centered, context-aware, and ethically grounded, ensuring that messages were easily understood and deeply internalized. His use of concise yet meaningful language, repetition for emphasis, gentle tone, and respectful engagement significantly enhanced the effectiveness of his message delivery.Furthermore, the study highlights the relevance of the Prophet’s communication principles in the modern era, particularly in education, leadership, media, and interpersonal relations. The research concludes that adopting prophetic communication ethics can contribute to more constructive dialogue, conflict resolution, and social cohesion in contemporary societies. This paper recommends the integration of prophetic communication principles into modern communication studies and professional training programs to promote ethical and effective human interaction.
Keywords: Prophetic Communication, Communication Ethics, Prophet Muhammad (PBUH), Islamic Communication, Speech Etiquette in Islam, Interpersonal Communication, Seerah Studies